"YOU NEVER HEARD JESUS SAY TO MAKE SURE YOU TAKE TIME OUT FOR YOURSELF": MILITARY CHAPLAINS AND THE STIGMA OF MENTAL ILLNESS. Issue 2 (November 2013) - Besterman‐Dahan, Karen; Lind, Jason D.; Crocker, Theresa; Besterman‐Dahan, Karen; Hamilton, Alison
<x xml:space="preserve">Abstract</x> The wars in Iraq and Afghanistan have taken a toll on military chaplains (MCs) who often return from deployment with high levels of stress, yet are expected to counsel on a daily basis without decompression of their own, potentially exacerbating any personal trauma. MC with posttraumatic stress disorder (PTSD) who have had deployments abridged due to their positive PTSD screen have reported shame due to leaving service members in their unit in danger while they went to safety. Many MCs report compassion fatigue, PTSD, reintegration issues, and adverse effects to their personal energy, motivation, and mental and spiritual well‐being postdeployment, related to stressors from deployment and combat exposure. Only 23–40 percent of Operation Enduring Freedom/Operation Iraqi Freedom/Operation New Dawn (OEF/OIF/OND) service members with a psychiatric disorder seek mental health care, citing stigma as a primary barrier. For MCs, stigma is compounded by a culture in which military health care providers, including MCs, are encouraged to deny their own needs to provide the necessary support to beneficiaries. This paper reviews a pilot study, which explored the impact of operational stress on the psychosocial health and reintegration of MCs, focusing on findings related to mental health and stigma within the military chaplaincy.